2020
DOI: 10.1038/s41598-020-72052-0
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-based vocal networks reveal social relationships in the Southern white rhinoceros

Abstract: Vocal communication networks can be linked to social behaviour, allowing a deeper understanding of social relationships among individuals. For this purpose, the description of vocal dyads is fundamental. In group-living species, this identification is based on behavioural indicators which require a high level of reactivity during social interactions. In the present study, we alternatively established a proximity-based approach to investigate whether sex-specific differences in vocal communication reflect socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…Vocalizations that due to ambient noises could not be reliably assigned to a call type or a sender were excluded from the analysis. A previous study ( Jenikejew et al , 2020 ) on vocal communication structure in SWR had demonstrated sex-specific differences in call rates for the contact call Pant (including its call variation Hic) as well as the agonistic call Hiss, emphasizing a relevant role of these two call types for mating behaviour. A further analysis in the present study therefore only included Pant and Hiss calls.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Vocalizations that due to ambient noises could not be reliably assigned to a call type or a sender were excluded from the analysis. A previous study ( Jenikejew et al , 2020 ) on vocal communication structure in SWR had demonstrated sex-specific differences in call rates for the contact call Pant (including its call variation Hic) as well as the agonistic call Hiss, emphasizing a relevant role of these two call types for mating behaviour. A further analysis in the present study therefore only included Pant and Hiss calls.…”
Section: Methodsmentioning
confidence: 97%
“…Besides, a conspicuous variation of the Pant call, also known as Hic, has been described as specifically characteristic during courtship, particularly for free-ranging bulls ( Cinková and Policht, 2016 ; Cinková and Shrader, 2020 ). A recently described sex difference in Pant call rates additionally indicates a socio-sexual function of this call type, with adult bulls panting significantly more often than adult females ( Jenikejew et al , 2020 ). A similar sex-specific variation in call rates has been also identified for the Hiss ( Jenikejew et al , 2020 ), a call type associated with agonistic interactions ( Owen-Smith, 1973 ; Policht et al , 2008 ), with females calling significantly more often than males.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Vocalizations were detected by auditory identification and categorized according to literature ( Cinková and Policht, 2014 ; Linn et al , 2018 ; Owen-Smith, 1973 ; Policht et al , 2008 ). For each vocalization, the respective call type, sender as well as potential receiver were noted (see Jenikejew et al , 2020 for a detailed description). Analysis focused on the contact call Pant and the agonistic call types Hiss and Grunt only, as a previous study demonstrated sex-specific differences in call rates, and hence a potentially relevant role in mating context for these call types ( Jenikejew et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Given the poor eyesight of rhinoceroses, this more pronounced social organization may favor a more complex acoustic communication system. Indeed, acoustic signals play an essential role in the coordination of mother–infant interactions ( Linn et al 2018 ), during friendly encounters, during aggressive interactions ( Owen-Smith 1973 ; Policht et al 2008 ; Jenikejew et al 2020 ), and during mating behavior of southern white rhinoceroses ( Owen-Smith 1973 ; Cinková and Shrader 2020 ). For example, vocalizations play a very important role in coordinating male and female behavior during consortship ( Owen-Smith 1973 ) where bulls follow a single cow for 2–3 weeks.…”
mentioning
confidence: 99%